Factors Predicting of Purchasing Decision Moslem Fashion Products in the New Normal Pandemic Covid-19 (Case Study in Madiun Municipality) - Tatik Mulyati; Arnedia Binada Duanti Putri (UNIVERSITAS PGRI MADIUN, 2020)
The economy and activities in various sectors and regions experienced a decline as a result of the Covid-19 pandemic. With a variety of limitations, the new normal period is a necessity and is an opportunity to carry out economic recovery and strengthening, including fashion products. This study aims to determine the factors that influence purchasing decisions for moslem fashion products on Instagram. The sample used as many as 250 people with sampling techniques using non-probability sampling methods. The data collection method uses a questionnaire. Analysis of the data used is Multiple Linear Regression Analysis. The results showed that there were 3 factors that influenced purchasing decisions on moslem fashion products on Instagram, namely electronic word of mouth (eWOM), information quality and celebrity endorsement. These three factors partially or simultaneously have a significant influence on purchasing decisions for fashion products on Instagram.